Faktor Faktor yang Mempengaruhi Profitabilitas Pada Perusahaan Food And Beverage Di BEI - Dimas Ramdhan Mahendra; Agustina Widodo (Universitas Islam Kadiri, 2023)
abstract This study aims to prove the effect of working capital turnover, cash turnover and liquidity on profitability in food and beverage companies listed on the Indonesia Stock Exchange. This study uses the dependent variable profitability, while the independent variables are working capital turnover, cash turnover and liquidity. Data collection techniques in this study used the documentation method with the sampling method, namely the purposive sampling method. The research sample consisted of 18 companies with 36 observations. The data analysis technique used was multiple linear regression analysis. Based on the results of the study, working capital turnover and cash turnover had no significant positive effect on profitability in food and beverage companies, while liquidity had a significant positive effect on profitability in food and beverage companies. The coefficient of determination (adjusted R2) is 0.083. This means that the independent variables, namely working capital turnover, cash turnover and liquidity in this regression model are able to explain the dependent variable profitability 11.6% while 91.7% is explained by other variables not examined in this research model.